Heat-conducting silica gel composition and preparation method of heat-conducting silica gel

By using composite fillers of nano-aluminum nitride and expanded graphite microsheets and a refined process, a multi-layered thermal conductive network is constructed, which solves the problems of insufficient heat dissipation and poor stability of traditional thermal conductive silicone. This achieves a comprehensive improvement in high-efficiency thermal conductivity, mechanical stability, and thermal and oxygen weather resistance, making it suitable for heat dissipation in high-power electronic devices.

CN120818245APending Publication Date: 2025-10-21厦门美塑新质科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511086116.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-04
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Traditional thermally conductive silicone rubber is difficult to meet the requirements of efficient thermal conductivity and long-term stable service due to poor filler dispersion and high interface thermal resistance. In addition, the role of the coupling agent in the hydrosilylation curing system is not precisely controlled, resulting in limited improvement in thermal conductivity, incomplete cross-linking, and poor thermal-oxidative stability.

Method used

A composite thermal conductive filler of nano-aluminum nitride and expanded graphite microsheets is used to construct a multi-level thermal conductive network by precisely controlling the particle size. γ-aminopropyltriethoxysilane coupling agent is used under humidity control to improve interfacial compatibility. Combined with the hydrosilylation curing process of hydrogenated silicone oil and vinyl silicone oil and a platinum catalyst, the reaction is ensured to proceed fully and form a stable three-dimensional network structure.

Benefits of technology

It significantly improves the thermal conductivity and mechanical properties of silicone compositions, enabling rapid heat dissipation from electronic components and ensuring their stable operation in high-temperature environments. It possesses excellent thermal stability and mechanical properties, meeting the heat dissipation requirements of high-power electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818245A_ABST
    Figure CN120818245A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heat-conducting silica gel, in particular to a heat-conducting silica gel composition and a heat-conducting silica gel preparation method. The high-temperature-resistant silicone rubber is prepared from the following components in parts by weight: 32 to 48 parts of vinyl silicone oil, 28 to 32 parts of nano aluminum nitride, 18 to 22 parts of expanded graphite microchips, 0.8 to 1.8 parts of gamma-aminopropyltriethoxysilane, 4.8 to 7.0 parts of hydrogen-containing silicone oil, 0.8 to 1.2 parts of hindered phenol antioxidant 1010 and 0.2 to 0.4 part of fatty acid polyethylene glycol ester. The particle sizes of the nano aluminum nitride and the expanded graphite microchips are precisely regulated and controlled, the nano aluminum nitride and the expanded graphite microchips synergistically construct a multi-layer heat conduction network, and the nano aluminum nitride effectively promotes heat conduction on the microscopic level by means of the high crystallinity and low interface thermal resistance of the nano aluminum nitride; and the expanded graphite microchips construct a heat conduction path on a macroscopic level by using a layered stacking structure of the expanded graphite microchips. The synergistic effect greatly reduces the interface thermal resistance in the heat transfer process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal conductive silicone rubber, and in particular to a thermal conductive silicone rubber composition and a method for preparing the thermal conductive silicone rubber. Background Art

[0002] With the rapid development of the electronic information industry, such as 5G base stations and new energy vehicle electronic control systems, the heat dissipation requirements for electronic components are becoming increasingly stringent.

[0003] Traditional thermally conductive silicone has poor filler dispersion and high interface thermal resistance, making it difficult to meet the requirements of efficient thermal conductivity and long-term stable service.

[0004] In the silicone system cured by hydrosilylation, the effect of the coupling agent depends on the hydrolysis environment. The existing process is not precisely controlled, the synergistic effect of the thermal conductive filler is not fully explored, and it is easy to agglomerate, resulting in limited improvement in thermal conductivity. The curing reaction often has problems such as incomplete cross-linking and poor thermal and oxidative stability due to the lack of catalysts or unreasonable parameters.

[0005] Therefore, the present invention particularly provides a thermally conductive silicone composition and a method for preparing the thermally conductive silicone. Summary of the Invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a thermally conductive silicone composition and a method for preparing thermally conductive silicone, aiming to solve the deficiencies in the prior art.

[0007] To achieve the above object, the present invention provides the following technical solution: a thermally conductive silicone composition, comprising the following components in parts by weight: 32-48 parts of vinyl silicone oil, 28-32 parts of nano-aluminum nitride, 18-22 parts of expanded graphite microplatelets, 0.8-1.8 parts of γ-aminopropyltriethoxysilane, 4.8-7.0 parts of hydrogenated silicone oil, 0.8-1.2 parts of hindered phenol antioxidant 1010, and 0.2-0.4 parts of fatty acid polyethylene glycol ester;

[0008] The particle size of the nano-aluminum nitride is 55-95 nm, the particle size of the expanded graphite microsheet is 12-18 μm, and the hydrogen content of the hydrogen-containing silicone oil is 0.16-0.19 wt %.

[0009] Preferably, the particle size of the nano-aluminum nitride is in the range of 55-95 nm, and preferably 65-85 nm. Preferably, the particle size of the expanded graphite microsheet is in the range of 12-18 μm, and preferably 14-16 μm.

[0010] The preparation method of thermal conductive silica gel is as follows:

[0011] S1: Place nano-aluminum nitride and expanded graphite microsheets into a high-speed blender, stir at 1100-1400 r / min, maintain the ambient humidity at 30-50% during the stirring process, add γ-aminopropyltriethoxysilane during the stirring process, continue stirring for 35-55 minutes, and then place in an oven at 85-95°C to dry for 2.5-3.5 hours;

[0012] S2: Add vinyl silicone oil to the interior of the reactor and stir at 550-750 r / min. Then add the nano-aluminum nitride and expanded graphite microsheets treated in S1 and stir for 1.2-1.8 hours. Then add fatty acid polyethylene glycol ester and continue stirring for 35-55 minutes.

[0013] S3: Transfer the mixture obtained in step S2 to a vacuum device and maintain a vacuum degree of 0.085-0.095 MPa for degassing for 20-25 minutes;

[0014] S4: Add hydrogenated silicone oil, hindered phenol antioxidant 1010 and platinum catalyst to the material treated in step S3 and stir, wherein the amount of the platinum catalyst is 0.001-0.005% of the mass of the vinyl silicone oil. After stirring evenly, inject into the mold and cure at 125°C-145°C for 1.2-1.8h to obtain thermal conductive silicone.

[0015] Preferably, the stirring speed of the thermal conductive filler pretreatment in step S1 is 1250.0-1350.0 r / min.

[0016] Preferably, the mixing and stirring speed in step S2 is 620-680 r / min.

[0017] Preferably, the vacuum degree of vacuum degassing in step S3 is 0.092-0.098 MPa.

[0018] Preferably, in step S4, the curing temperature is 132-138° C., and the curing time is 1.4-1.6 h.

[0019] Preferably, the total mass ratio of the γ-aminopropyltriethoxysilane to the nano-aluminum nitride and expanded graphite microsheets is 0.015-0.035:1.

[0020] Preferably, the weight ratio of the hydrogen-containing silicone oil to the vinyl silicone oil is 0.10-0.25:1.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. This invention precisely controls the particle size of nano-aluminum nitride and expanded graphite microplatelets, allowing them to synergistically construct a multi-layered thermal network. Nano-aluminum nitride, with its high crystallinity and low interfacial thermal resistance, effectively promotes heat conduction at the microscopic level; while the expanded graphite microplatelets, with their layered stacking structure, create a thermal path at the macroscopic level. This synergistic effect significantly reduces interfacial thermal resistance during heat transfer and significantly improves the thermal conductivity of the silicone composition. This allows for rapid heat dissipation during the operation of electronic components, ensuring their stable operation in high-temperature environments and effectively preventing performance degradation and lifespan reduction caused by heat accumulation. This provides fundamental support for the reliable operation of high-power electronic devices.

[0023] 2. The present invention clarifies the working environment and process of γ-aminopropyltriethoxysilane coupling agent. With the help of trace water provided by ambient humidity, the hydrolysis reaction of the coupling agent is promoted. One end of the hydrolyzed coupling agent is combined with inorganic fillers such as nano-aluminum nitride, and the other end is connected to the vinyl silicone oil organic matrix, effectively improving the interfacial compatibility between the inorganic filler and the organic matrix. This not only inhibits the agglomeration of the filler, ensures the uniform dispersion of the filler in the matrix, and improves the mechanical properties of the silicone composition, but also enhances the smoothness of heat transfer and further improves thermal stability, so that the silicone can still maintain good thermal conductivity and mechanical properties under complex environments such as long-term hot and cold cycles.

[0024] 3. The present invention improves the hydrosilylation curing process of hydrogenated silicone oil and vinyl silicone oil, supplements a platinum catalyst to ensure efficient reaction, and allows the silicone to fully cross-link within the set temperature and time to form a stable three-dimensional network structure; combined with the synergistic effect of hindered phenolic antioxidants, it captures free radicals generated in high-temperature environments and delays the oxidative degradation of the polymer; this allows the silicone composition to have excellent thermal and oxygen stability after curing and molding, and can serve for a long time in high-temperature, high-load electronic equipment heat dissipation scenarios, meeting the heat dissipation needs of high-power electronic equipment and reducing the risk of equipment failure due to material performance degradation. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a process flow chart of the method for preparing thermal conductive silica gel of the present invention. DETAILED DESCRIPTION

[0026] For the convenience of understanding the present invention, the present invention is given below with examples. It should be understood by those skilled in the art that the examples are only for the purpose of helping to understand the present invention and should not be regarded as specific limitations of the present invention.

[0027] The raw materials used can all be purchased on the market.

[0028] Example 1

[0029] Raw materials: 32 parts vinyl silicone oil, 28 parts nano-aluminum nitride with a particle size of 55.0 nm, 18 parts expanded graphite microplatelets with a particle size of 12 μm, 0.8 parts γ-aminopropyltriethoxysilane, 4 parts hydrogenated silicone oil with a hydrogen content of 0.16 wt%, 0.8 parts hindered phenol antioxidant 1010, 0.2 parts fatty acid polyethylene glycol ester, and a platinum catalyst (the amount of platinum catalyst is 0.001% by weight of the vinyl silicone oil).

[0030] Preparation: Place nano-aluminum nitride and expanded graphite microsheets into a high-speed blender separately, ensuring that the blender is clean and free of impurities.

[0031] The mixer was turned on and the stirring speed was precisely adjusted to 1100 r / min. During the entire stirring process, the ambient humidity was maintained at 30% by the ambient humidity control device.

[0032] Slowly add γ-aminopropyltriethoxysilane to ensure that it can be evenly dispersed in the filler, and continue stirring for 35 minutes to allow the coupling agent to fully contact and react with the surface of nano-aluminum nitride and expanded graphite microsheets. After stirring, transfer the material intact to the oven, set the oven temperature to 85°C, and dry it for 2.5 hours to complete the surface modification of the filler. After taking it out, cool it to room temperature.

[0033] Add the weighed vinyl silicone oil into the clean reactor, start the stirring device of the reactor, and set the stirring speed to 550r / min.

[0034] The nano-aluminum nitride and expanded graphite microsheets treated as above were sequentially added into the reactor. Note that the addition process should be slow and even to avoid local agglomeration. Stir for 1.2 hours to allow the fillers to be initially dispersed in the vinyl silicone oil matrix.

[0035] Then, fatty acid polyethylene glycol ester was added and stirring was continued for 35 min to further promote uniform dispersion of the filler.

[0036] Transfer the mixed material to the vacuum degassing equipment, close the equipment door, start the vacuum system, adjust the vacuum degree to 0.085MPa, and maintain the vacuum degree for degassing for 20 minutes to remove the bubbles generated by stirring in the material.

[0037] After degassing, the material was taken out, and hydrogenated silicone oil, hindered phenol antioxidant 1010 and a calculated amount of platinum catalyst were added thereto, and the mixture was stirred thoroughly with a stirrer until all the components were evenly mixed.

[0038] Pour the mixed material into the pre-cleaned mold, taking care to avoid spillage. Place the mold in a curing oven, set the curing temperature to 125°C, and maintain this temperature for 1.2 hours. After curing is complete, turn off the curing oven and wait for the mold to cool to room temperature before removing the formed thermally conductive silicone.

[0039] Example 2

[0040] Raw materials: 35 parts vinyl silicone oil, 30 parts 70 nm nano-aluminum nitride, 20 parts 15 μm expanded graphite flakes, 1.3 parts γ-aminopropyltriethoxysilane, 5.5 parts hydrogenated silicone oil with a hydrogen content of 0.17 wt%, 1 part hindered phenol antioxidant 1010, 0.3 parts fatty acid polyethylene glycol ester, and a platinum catalyst (the amount of platinum catalyst is 0.003% by weight of the vinyl silicone oil).

[0041] Preparation: Place nano-aluminum nitride and expanded graphite microsheets into a high-speed blender. Check that the blender blades are intact. Turn on the blender and adjust the stirring speed to 1250 r / min. Maintain the ambient humidity at 40% using humidity control.

[0042] While stirring, add γ-aminopropyltriethoxysilane gradually to ensure that it is in full contact with the filler, and continue stirring for 45.0 minutes. After the stirring is completed, transfer the material to an oven and dry it at 90°C for 3.0 hours to complete the surface modification, and cool it for use.

[0043] Add vinyl silicone oil into the reactor, start stirring, set the stirring speed to 650r / min, slowly add the pretreated nano-aluminum nitride and expanded graphite microsheets into the reactor in turn, observe the dispersion while adding, stir for 1.5h, add fatty acid polyethylene glycol ester, and continue stirring for 45min to make the filler more evenly dispersed in the matrix.

[0044] The mixture was transferred to a vacuum degassing device and evacuated to 0.090 MPa. The vacuum was maintained for 22 minutes to remove air bubbles from the mixture. After degassing, hydrogenated silicone oil, hindered phenol antioxidant 1010, and platinum catalyst were added to the mixture and stirred thoroughly until the mixture was uniform.

[0045] Pour the material into the mold and place it in the curing oven. Set the curing temperature to 135°C and cure for 1.5 hours. After curing, wait for the mold to cool and then remove the finished thermal conductive silicone product.

[0046] Example 3

[0047] Raw materials: 38 parts vinyl silicone oil, 32 parts 95nm nano-aluminum nitride, 22 parts 18μm expanded graphite flakes, 1.8 parts γ-aminopropyltriethoxysilane, 7 parts hydrogenated silicone oil with a hydrogen content of 0.19wt%, 1.2 parts hindered phenol antioxidant 1010, 0.4 parts fatty acid polyethylene glycol ester, and a platinum catalyst (the amount of platinum catalyst is 0.005% by weight of the vinyl silicone oil).

[0048] Preparation: Add nano-aluminum nitride and expanded graphite flakes into a high-speed mixer respectively to ensure the normal operation of the equipment.

[0049] Turn on the mixer, adjust the stirring speed to 1400r / min, maintain the ambient humidity at 50%, and evenly add γ-aminopropyltriethoxysilane during the stirring process. Continue stirring for 55 minutes, then put the material into an oven and dry it at 95°C for 3.5 hours to complete the surface modification treatment, and cool it to room temperature.

[0050] Add vinyl silicone oil to the reactor, start the stirring device, set the stirring speed to 750r / min, put the pretreated nano-aluminum nitride and expanded graphite microsheets into the reactor in turn, stir for 1.8h, add fatty acid polyethylene glycol ester, and continue stirring for 55min to optimize the filler dispersion effect.

[0051] The mixed material was transferred to a vacuum degassing device, the vacuum degree was adjusted to 0.095 MPa, and degassing was carried out for 25 minutes. After degassing, hydrogenated silicone oil, hindered phenol antioxidant 1010 and platinum catalyst were added to the material and stirred thoroughly.

[0052] The material was injected into the mold and placed in a curing oven to cure at 145°C for 1.8 hours. After curing, the mold was cooled and the thermal conductive silicone was removed.

[0053] Example 4

[0054] Raw materials: 33 parts vinyl silicone oil, 29 parts nano-aluminum nitride with a particle size of 60.0 nm, 19 parts expanded graphite microplatelets with a particle size of 13 μm, 1 part γ-aminopropyltriethoxysilane, 4.5 parts hydrogenated silicone oil with a hydrogen content of 0.165 wt%, 0.9 part hindered phenol antioxidant 1010, 0.25 parts fatty acid polyethylene glycol ester, and a platinum catalyst (the amount of platinum catalyst is 0.002% by weight of the vinyl silicone oil).

[0055] Preparation: Place nano-aluminum nitride and expanded graphite microsheets into a high-speed blender respectively and check whether the equipment is normal.

[0056] Turn on the mixer, adjust the stirring speed to 1150 r / min, maintain the ambient humidity at 35%, slowly add γ-aminopropyltriethoxysilane while stirring, continue stirring for 40 minutes, then transfer the material to an oven, dry it at 88°C for 2.8 hours to complete the surface modification, and cool it for later use.

[0057] Add vinyl silicone oil to the reactor and start stirring at a speed of 580r / min. Add the pretreated nano-aluminum nitride and expanded graphite microsheets into the reactor in turn. After stirring for 1.3h, add fatty acid polyethylene glycol ester and continue stirring for 40min to promote filler dispersion.

[0058] The mixture was transferred to a vacuum degassing device, evacuated to 0.088 MPa, and degassed for 21 minutes. After degassing, hydrogenated silicone oil, hindered phenol antioxidant 1010, and platinum catalyst were added and stirred evenly.

[0059] The material was injected into the mold, placed in a curing oven, and cured at 128°C for 1.3 hours. After curing, the thermal conductive silicone was removed after cooling.

[0060] Example 5

[0061] Raw materials: 36 parts vinyl silicone oil, 31 parts 80.0 nm nano-aluminum nitride, 21 parts 17 μm expanded graphite flakes, 1.5 parts γ-aminopropyltriethoxysilane, 6 parts 0.18 wt% hydrogen-containing silicone oil, 1.1 parts hindered phenol antioxidant 1010, 0.35 parts fatty acid polyethylene glycol ester, and a platinum catalyst (the amount of platinum catalyst is 0.004% by weight of the vinyl silicone oil).

[0062] Preparation: Place nano-aluminum nitride and expanded graphite microsheets into a high-speed blender respectively, and ensure that there are no abnormalities in the equipment.

[0063] Turn on the mixer, adjust the stirring speed to 1300 r / min, maintain the ambient humidity at 45%, gradually add γ-aminopropyltriethoxysilane during the stirring process, continue stirring for 50 minutes, then transfer the material to an oven, dry it at 92°C for 3.2 hours to complete the surface modification, and cool it to room temperature.

[0064] Add vinyl silicone oil into the reactor, start stirring at 700r / min, put the pretreated nano-aluminum nitride and expanded graphite microsheets into the reactor in turn, stir for 1.6h, add fatty acid polyethylene glycol ester, and continue stirring for 50min to evenly disperse the filler.

[0065] The mixed material was transferred to a vacuum degassing device, the vacuum degree was adjusted to 0.093 MPa, and degassing was performed for 23 minutes. After degassing, hydrogenated silicone oil, hindered phenol antioxidant 1010 and platinum catalyst were added to the material and stirred thoroughly.

[0066] The material was injected into the mold, placed in a curing oven, and cured at 140°C for 1.6 hours. After curing, the mold was cooled and the finished thermal conductive silicone product was taken out.

[0067] The test data of Examples 1-5 and Comparative Examples 1-2 are shown in Tables 1 and 2.

[0068] In Comparative Example 1, the composite thermal conductive filler system of nano-aluminum nitride and expanded graphite microsheets was not used, and only a single thermal conductive filler was used, such as only nano-aluminum nitride or only expanded graphite microsheets.

[0069] In Comparative Example 2, the ambient humidity of the coupling agent was not controlled, and no platinum catalyst was added, resulting in incomplete hydrolysis of the coupling agent, insufficient hydrosilylation reaction, poor filler dispersion, and low degree of crosslinking.

[0070] Table 1 - Test results of Examples 1-5 and Comparative Examples 1-2

[0071] project Thermal conductivity (W / (m·k) Tensile strength (MPa) Elongation at break (%) Example 1 3.2 1.8 280 Example 2 3.8 2.1 310 Example 3 3.5 2.0 290 Example 4 3.3 1.9 285 Example 5 3.6 2.0 300 Comparative Example 1 1.5 1.2 180 Comparative Example 2 2.0 1.0 150

[0072] Table 2 - Test results of Examples 1-5 and Comparative Examples 1-2

[0073]

[0074] Based on the above data, the following conclusions can be drawn:

[0075] First, a composite thermally conductive filler system of "nano-aluminum nitride + expanded graphite microplatelets" was used to precisely control particle size, achieving the coordinated construction of a multi-layered thermal network. Test data showed that the thermal conductivities of Examples 1-5 were all between 3.2-3.8 W / (m·K), while the thermal conductivity of Comparative Example 1, which used a single filler, was only 1.5 W / (m·K), a significant difference.

[0076] Nano-aluminum nitride, with its high crystallinity and low interfacial thermal resistance, fills the gaps in the matrix at the micro level and reduces heat transfer barriers; expanded graphite microsheets build continuous heat conduction pathways at the macro level with a layered stacking structure. The two form a "micro-macro" complementary heat conduction network, significantly reducing interfacial thermal resistance.

[0077] At the same time, the γ-aminopropyltriethoxysilane coupling agent is fully hydrolyzed under 30-50% humidity conditions, with one end combining with the inorganic filler and the other end connecting with the vinyl silicone oil matrix, effectively improving the interfacial compatibility. The tensile strength of Examples 1-5 reaches 1.8-2.1 MPa, and the elongation at break is 280-310%, which is much higher than that of Comparative Example 1, confirming the improvement of filler dispersion and interfacial bonding strength.

[0078] Second, refined control of the preparation process is another important support for the performance advantages of the present invention. By regulating the stirring speed, ambient humidity, vacuum degree and curing conditions, and introducing a platinum catalyst, the reaction sufficiency and structural stability are ensured.

[0079] Comparison with the test data of Comparative Example 2 shows that the thermal conductivity of Comparative Example 2 is only 2.0 W / (m·K), the thermal weight loss rate is 2.0%, and the thermal conductivity retention rate after hot and cold cycles is only 70%;

[0080] The thermal weight loss rate of Examples 1-5 is only 0.6-0.8%, and the thermal cycle retention rate is 95-97%. This is because humidity control promotes the hydrolysis of the coupling agent and prevents filler agglomeration; the platinum catalyst accelerates the hydrosilylation reaction, ensuring complete cross-linking and forming a stable three-dimensional network; vacuum degassing reduces the obstruction of bubbles to heat conduction and improves the density of the material.

[0081] 3. The thermally conductive silicone composition of the present invention has excellent performance in thermal conductivity, mechanical properties, thermal stability and insulation. The thermal conductivity is 2-2.5 times that of traditional single-filler silicone, and the tensile strength is increased by more than 50%.

[0082] These performance advantages enable it to effectively solve the pain points of "insufficient heat dissipation and poor stability" of traditional thermal conductive silicone. In high-temperature and high-load scenarios such as 5G base station power devices and new energy vehicle electronic control modules, it can quickly dissipate accumulated heat to prevent device failure due to overheating; at the same time, excellent hot and cold cycle stability ensures long-term service reliability and reduces equipment maintenance costs.

[0083] In summary, the present invention achieves a comprehensive improvement in the "efficient thermal conductivity - mechanical stability - thermal and oxygen weathering resistance" of thermal conductive silicone through the synergy of composite fillers and precise process control, providing a reliable material solution for heat dissipation of high-power electronic equipment.

[0084] Throughout this specification, references to terms such as "one embodiment," "example," and "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.

[0085] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to the specific embodiments described. Obviously, numerous modifications and variations are possible based on the contents of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention.

Claims

1. A thermally conductive silicone composition, characterized in that: The invention is composed of the following components in parts by weight: 32-48 parts of vinyl silicone oil, 28-32 parts of nano-aluminum nitride, 18-22 parts of expanded graphite microplatelets, 0.8-1.8 parts of γ-aminopropyltriethoxysilane, 4.8-7.0 parts of hydrogenated silicone oil, 0.8-1.2 parts of hindered phenol antioxidant 1010, and 0.2-0.4 parts of fatty acid polyethylene glycol ester; The particle size of the nano-aluminum nitride is 55-95 nm, the particle size of the expanded graphite microsheet is 12-18 μm, and the hydrogen content of the hydrogen-containing silicone oil is 0.16-0.19 wt %.

2. The thermally conductive silicone composition according to claim 1, characterized in that: The particle size of the nano-aluminum nitride is in the range of 55-95 nm, and preferably 65-85 nm.

3. The thermally conductive silicone composition according to claim 1, characterized in that: The particle size of the expanded graphite flakes is 12-18 μm, and preferably 14-16 μm.

4. A method for preparing thermally conductive silica gel according to claims 1-3, characterized in that: The preparation method of the thermal conductive silica gel is as follows: S1: Place nano-aluminum nitride and expanded graphite microsheets into a high-speed blender, stir at 1100-1400 r / min, maintain the ambient humidity at 30-50% during the stirring process, add γ-aminopropyltriethoxysilane during the stirring process, continue stirring for 35-55 minutes, and then place in an oven at 85-95°C to dry for 2.5-3.5 hours; S2: Add vinyl silicone oil to the interior of the reactor and stir at 550-750 r / min. Then add the nano-aluminum nitride and expanded graphite microsheets treated in S1 and stir for 1.2-1.8 hours. Then add fatty acid polyethylene glycol ester and continue stirring for 35-55 minutes. S3: Transfer the mixture obtained in step S2 to a vacuum device and maintain a vacuum degree of 0.085-0.095 MPa for degassing for 20-25 minutes; S4: Add hydrogenated silicone oil, hindered phenol antioxidant 1010 and platinum catalyst to the material treated in step S3 and stir, wherein the amount of the platinum catalyst is 0.001-0.005% of the mass of the vinyl silicone oil. After stirring evenly, inject into the mold and cure at 125°C-145°C for 1.2-1.8h to obtain thermal conductive silicone.

5. The method for preparing thermally conductive silica gel according to claim 4, characterized in that: The stirring speed of the thermal conductive filler pretreatment in step S1 is 1250.0-1350.0 r / min.

6. The method for preparing thermally conductive silica gel according to claim 4, characterized in that: The mixing and stirring speed in step S2 is 620-680 r / min.

7. The method for preparing thermally conductive silica gel according to claim 4, characterized in that: The vacuum degree of the vacuum degassing in the step S3 is 0.092-0.098 MPa.

8. The method for preparing thermally conductive silica gel according to claim 4, characterized in that: In the step S4, the curing temperature is 132-138° C., and the curing time is 1.4-1.6 hours.

9. The thermally conductive silicone composition according to claim 1, characterized in that: The total mass ratio of the gamma-aminopropyltriethoxysilane to the nano-aluminum nitride and the expanded graphite microsheets is 0.015-0.035:

1.

10. The thermally conductive silicone composition according to claim 1, wherein The weight ratio of the hydrogen-containing silicone oil to the vinyl silicone oil is 0.10-0.25:1.